Comparison of two manipulative techniques on pain and function in patients with low back pain: a double-blind clinical trial - Figueiredo Moreira, Felipe; Patel, Raissa; Alfredo Braun Ferreira, Luiz; Wagner Menna; Luciano Pavan Rossi (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Low back pain affects a large part of the population, exerting negative impacts on the physical, social and emotional aspects of quality of life. Manipulative therapy is one of the main techniques used in the treatment, but little is known whether one technique is a more effective than another in terms of improving low back pain and functioning. Objectives: Compare two physiotherapeutic manipulation techniques (Maitland concept vs. osteopathy) and determine the impact on pain and functioning in patients with chronic low back pain. Methods: Forty-eight patients with nonspecific chronic low back pain (age: 18 to 40 years) and no contraindication for manipulation techniques participated in the study. Intervention: A single manipulation was performed in the lumbar region of the patients allocated to the Maitland group and osteopathy group. Randomization was performed using the Random Number Generator v.3.0.72 with concealed allocation. Blinding: The assessor who collected all data and the participants were blinded to the allocation to the different groups. Outcomes: Pain intensity (VAS), pressure pain threshold (algometer) and functional capacity (Roland-Morris) seven and 30 days after manipulation. Results: Both groups exhibited an improvement in the pressure pain threshold after seven days, which was maintained at 30 days. Likewise, the two groups exhibited an improvement in functional capacity after seven days, but this result was only maintained at 30 days in the Maitland group. No difference in pain intensity was found in either group after manipulation. No significant differences were found between the osteopathy and Maitland groups for any of the outcomes of interest. Conclusion: Although both methods led to improvements in the pressure pain threshold and functional capacity of the lumbar spine, no significant differences were found between the osteopathic and Maitland manipulation treatment techniques for the pain and functional capacity outcomes in patient with chronic low back pain.